A Case of Non-simultaneous Bilateral Partial Triceps Tendon Repair. Issue 3 (27th December 2017) - Goodrich, Eric; Goodrich, Richard P
Abstract: A partial triceps tendon tear is an uncommon injury. Even rarer is a bilateral partial triceps tendon tear in which there has been one documented case. This case report illustrates a 37-yr-old African-American male who sustained non-simultaneous bilateral partial triceps tendon avulsions. He sustained a traumatic right partial triceps tendon avulsion after a fall onto an outstretched right arm that required operative repair after failure of conservative treatment. Five months later, he sustained a similar injury after falling on an outstretched left arm that was repaired 9 d later. His post-operative courses were uncomplicated. He returned to full duty at his 6 mo and remained symptom free at 12 mo. The case demonstrates that operative treatment of partial triceps tendon avulsions using bone tunnels yields good outcomes in high-demand patients who have failed conservative treatment and who have had an operative repair of the contralateral extremity.